Strength analysis of Cranioplasty PMMA flap material. (2019) - Archana, R.; Baldia, Manish; Jeeva, J.B.; Devakumar,; Joseph, Mathew
Abstract: Cranial defects are restored by surgical procedure called Cranioplasty and flaps were made using Poly Methyl Metha Acrylate (PMMA) material to fill the defect. PMMA flaps with different thickness and monomer compositions were made and strength analysis was performed. Samples with thickness of 9mm having highest dilution and samples with thickness of 5mm and lowest dilution were found to have skull bone equivalent strength. In Cranioplasty, the thickness of the flap does not exceed 5mm which corresponds to average skull bone thickness. Therefore it was concluded that the sample with 3mm thickness and composition of 1:1 was found to have high compressive strength (50.08MPa) and flexural strength (76.73MPa) respectively.